1990
DOI: 10.1246/bcsj.63.1985
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Coordination Sites in Ni(II), Zn(II), and Cd(II) Complexes with 7-[(3,5-Dichloro(or bromo)-2-pyridyl)azo]-8-hydroxyquinoline-5-sulfonic Acid

Abstract: A new multidentate ligand, 7-[(3,5-dichloro(or bromo)-2-pyridyl)azo]-8-hydroxyquinoline-5-sulfonic acid (sodium salt, abbr. as 3,5-di-X-PAHQS, X=Cl or Br) which contains pyridylazonaphthol (PAN) and 8-quinolinol skeletons, was prepared for the first time in order to investigate its coordination behavior toward metal(II) ions. For comparative studies, the ligands (2-[(3,5-dichloro(or bromo)-2-pyridyl)azo]-1-hydroxynaphthalene-4-sulfonic acid (sodium salt, abbr. as 3,5-di-X-αPANS, X=Cl or Br), 1-[(3,5-dichloro(o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…(C 16 H 11 N 4 O 7 SNa)Na: calcd, 5.39, found, 4.03. The sodium content of the sample indicated that the monosodium salt (sulfonate) was the major component in agreement with literature data for structurally related compounds. , The IR spectrum showed the presence of water; similar compounds were reported to crystallize with various amounts of water. , The water content contributed to the difference between the sodium content of the sample and the calculated amount for the anhydrous monosodium salt. Thus, the general formula C 16 H 12 - x N 4 O 7 SNa x ·(H 2 O) y was proposed for the components of this product.…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…(C 16 H 11 N 4 O 7 SNa)Na: calcd, 5.39, found, 4.03. The sodium content of the sample indicated that the monosodium salt (sulfonate) was the major component in agreement with literature data for structurally related compounds. , The IR spectrum showed the presence of water; similar compounds were reported to crystallize with various amounts of water. , The water content contributed to the difference between the sodium content of the sample and the calculated amount for the anhydrous monosodium salt. Thus, the general formula C 16 H 12 - x N 4 O 7 SNa x ·(H 2 O) y was proposed for the components of this product.…”
Section: Methodssupporting
confidence: 86%
“…Consistent with this observation, Hirohata et al found that a multidentate azo dye formed chelates with more metal ions than a structurally related bidentate azo compound 13b. The structure and stability of the chelate(s) formed between an azo dye and a metal ion depend on a number of factors including the size of the chelate ring(s), the number of chelate rings per molecule, steric restrictions, the basicity of the ligand, and the nature of the metal. 7a,13a The hard and soft acid and base (HSAB) properties of the chelating sites and metal ion strongly influence the coordination mode of a multidentate ligand toward a metal ion, when multiple types of chelates can be formed. ,,
5 Absorbance spectra of chelates of dye 4aak with selected metal ions.
6 Absorbance spectra of chelates of dye 4iab with selected metal ions.
7 Absorbance spectra of chelates of dye 4aah with selected metal ions.
…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations